Distribution of Stromal Cell Subsets in Cultures from Distinct Ocular Surface Compartments - Liu, Lei; Yu, Ying; Peng, Qiuyue; Porsborg, Simone R; Nielsen, Frederik M; Jørgensen, Annemette; Grove, Anni; Bath, Chris; Hjortdal, Jesper; Christiansen, Ole B; Fink, Trine; Zachar, Vladimir (Journal of Ophthalmic and Vision Research, 2020)
Purpose: To reveal the phenotypic differences between human ocular surface stromal cells (hOSSCs) cultured from the corneal, limbal, and scleral compartments. Methods: A comparative analysis of cultured hOSSCs derived from four unrelated donors was conducted by multichromatic flow cytometry for six distinct CD antigens, including the CD73, CD90, CD105, CD166, CD146, and CD34. Results: The hOSSCs, as well as the reference cells, displayed phenotypical profiles that were similar in high expression of the hallmark mesenchymal stem cell markers CD73, CD90, and CD105, and also the cancer stem cell marker CD166. Notably, there was considerable variation regarding the expression of CD34, where the highest levels were found in the corneal and scleral compartments. The multi-differentiation potential marker CD146 was also expressed highly variably, ranging from 9% to 89%, but the limbal stromal and endometrial mesenchymal stem cells significantly surpassed their counterparts within the ocular and reference groups, respectively. The use of six markers enabled investigation of 64 possible variants, however, just four variants accounted for almost 90% of all hOSSCs, with the co-expression of CD73, CD90, CD105, and CD166 and a combination of CD146 and CD34. The limbal compartment appeared unique in that it displayed greatest immunophenotype diversity and harbored the highest proportion of the CD146+CD34- pericyte-like forms, but, interestingly, the pericyte-like cells were also found in the avascular cornea. Conclusions: Our findings confirm that the hOSSCs exhibit an immunophenotype consistent with that of MSCs, further highlight the phenotypical heterogeneity in stroma from distinct ocular surface compartments, and finally underscore the uniqueness of the limbal region.